Jurnal Ilmu Pengetahuan Sosial: Pemanfaatan Media Pembelajaran Audio Visual dalam Pembelajaran IPS untuk Meningkatkan Hasil Belajar Siswa di SMP - Padmasari, Azizah; Desy Safitri; Sujarwo (PT. Intelek Cendikiawan Nusantara, 2024)
Learning using audiovisual media is an alternative in learning using media that contains elements of sound and images, which involves the senses of sight and hearing. Learning media has an important role in improving elementary school student learning outcomes. Using audio-visual media can help in the Social Sciences learning process for elementary school students. The aim of this research is to find out the benefits of using audio-visual media in social studies learning for elementary school students. The social studies learning process is usually focused on the teacher, because there is a lack of improvisation so there is no other improvisation which causes students to tend to feel bored and only listen to the main material. So teachers need to use interesting learning media in order to improve the quality of students' learning outcomes in social studies scores. This research is based on the researcher's curiosity about the use of audiovisual learning media in junior high schools. The use of audiovisual based learning media is based on the problem of low student learning outcomes in the learning process which causes students to be less active in paying attention to lessons. This research uses qualitative descriptive research with the Literature Review research type. data obtained by analyzing journals related to the researcher's title, namely the use of audiovisual media in social studies learning on student learning outcomes in junior high schools. Keywords : Learning Media, Audio Visual, Social Studies learning Abstrak Pembelajaran menggunakan media Audiovisual adalah salah satu alternatif dalam pembelajaran dengan menggunakan media yang mengandung unsur suara dan gambar, di mana melibatkan Indera penglihatan dan pendengaran. Media pembelajaran mempunyai peran penting dalam meningkatkan hasil belajar siswa Sekolah Dasar. Dengan penggunaan media audio visual dapat membantu dalam proses pembelajaran Ilmu Pengetahuan Sosial siswa sekolah dasar. Tujuan dari penelitian ini adalah untuk mengetahui apa manfaat menggunakan media audio visual dalam pembelajaran IPS bagi siswa sekolah menengah pertama. Proses pembelajaran IPS biasanya terfokus pada guru, karena kurangnya improvisasi sehingga tidak adanya improvisasi lain yang menyebabkan siswa cenderung merasa bosan dan hanya terpaku pada materi pokok saja. Maka guru perlu menggunakan media pembelajaran yang menarik agar dapat meningkatkan kualitas hasil belajar peserta didik dalam nilai IPS. Penelitian ini didasari oleh ke ingin tahuan peneliti dalam pemanfaatan media pembelajaran audiovisual di SMP, Pemanfaatan media pembelajaran berbasis audio visual didasari adanya masalah rendahnya hasil belajar peserta didik dalam proses pembelajaran yang menyebabkan peserta didik kurang aktif dalam memperhatikan pelajaran. Penelitian ini menggunakan penelitian kualitatif deskriptif dengan jenis penelitian Literature Review. data yang didapatkan dengan menganalisis jurnal yang berkaitan dengan judul peneliti yaitu Penggunaan Media Audiovisual dalam Pembelajaran IPS terhadap hasil belajar siswa di SMP. Kata Kunci : Media Pembelajaran, Audio Visual, Pembelajaran IPS